Perinatal Mortality and Related Obstetric Risk Factors in Dhaka National Medical College Hospital (Journal of Dhaka National Medical College & Hospital, 2014)
Objective: To determine perinatal mortality and its related risk factors in Dhaka National Medical College Hospital.Study design: Prospective observational study.Setting: Obstetrics and Gynaecology Department in Dhaka National Medical College Hospital from January to December 2011.Patients and Methods: All perinatal deaths including stillbirths (SBs) and early neonatal deaths (ENNDs) within 0-7 days of delivery after 28 wks of gestation were studied during the study period, while pregnancies